A Primer on Nonmarket Valuation - Champ, Patricia A.; Boyle, Kevin J.; Brown, Thomas C. (The Economics of Non-Market Goods and Resources ;, 2003)
A Primer on Nonmarket Valuation is unique in its clear descriptions of the most commonly used nonmarket valuation techniques and their implementation. Individuals working for government agencies, attorneys involved with natural resource damage assessments, graduate students, and others will appreciate the non-technical and practical tone of this book. The first section of the book provides the context and theoretical foundation of nonmarket valuation, along with practical data issues. The middle two sections of the Primer describe the major stated and revealed nonmarket valuation techniques. For each technique, the steps involved in implementation are laid out and described. Both practitioners of nonmarket valuation and those who are new to the field will come away from these methods chapters with a thorough understanding of how to design, implement, and analyze a nonmarket valuation study.